Influenza: prevention, prophylaxis and treatment - Roxane Jones; Stuart Jones (South African Family Practice)
Influenza spreads rapidly to affect 515% of the global population on an annual basis. It is estimated that influenza causes between three and five million cases of severe illness and between a quarter and half a million deaths every year. In South Africa during the period from 1997 to 2001, influenza and pneumonia combined was one of the top five causes of death for both males and females.1 Influenza illness causes substantial morbidity and mortality, with healthcare costs and lost productivity due to absenteeism resulting in both direct and indirect costs and, ultimately, a formidable economic burden.2